Serial H3K27M cell-free tumor DNA (cf-tDNA) tracking predicts ONC201 treatment response and progression in diffuse midline glioma. Issue 8 (6th February 2022) - Cantor, Evan; Wierzbicki, Kyle; Tarapore, Rohinton S; Ravi, Karthik; Thomas, Chase; Cartaxo, Rodrigo; Nand Yadav, Viveka; Ravindran, Ramya; Bruzek, Amy K; Wadden, Jack; John, Vishal; May Babila, Clarissa; et al.
Abstract: Background: Diffuse Midline Glioma (DMG) with the H3K27M mutation is a lethal childhood brain cancer, with patients rarely surviving 2 years from diagnosis. Methods: We conducted a multi-site Phase 1 trial of the imipridone ONC201 for children with H3K27M-mutant glioma (NCT03416530). Patients enrolled on Arm D of the trial ( n = 24) underwent serial lumbar puncture for cell-free tumor DNA (cf-tDNA) analysis and patients on all arms at the University of Michigan underwent serial plasma collection. We performed digital droplet polymerase chain reaction (ddPCR) analysis of cf-tDNA samples and compared variant allele fraction (VAF) to radiographic change (maximal 2D tumor area on MRI). Results: Change in H3.3K27M VAF over time ("VAF delta") correlated with prolonged PFS in both CSF and plasma samples. Nonrecurrent patients that had a decrease in CSF VAF displayed a longer progression free survival ( P = .0042). Decrease in plasma VAF displayed a similar trend ( P = .085). VAF "spikes" (increase of at least 25%) preceded tumor progression in 8/16 cases (50%) in plasma and 5/11 cases (45.4%) in CSF. In individual cases, early reduction in H3K27M VAF predicted long-term clinical response (>1 year) to ONC201, and did not increase in cases of later-defined pseudo-progression. Conclusion: Our work demonstrates the feasibility and potential utility of serial cf-tDNA in both plasma and CSF of DMG patients to supplement radiographic monitoring. Patterns of change in H3K27M VAF over time demonstrate clinical utility in terms of predicting progression and sustained response and possible differentiation of pseudo-progression and pseudo-response.